Kidscreen -52: parents perception of their childrens quality of life - Matos,Margarida Gaspar de (2013)
The KIDSCREEN 52 is a European cross-cultural and standardized instrument that assesses ten health related quality of life (HRQoL) dimensions in children, adolescents and their parents. It is often claimed that children self reports are not totally accurate, calling for a confirmation from parents or caregivers. The present study focuses only on the Kidscreen-52, parents version (a parallel version addressed specifically to parents perceptions of their sons HRQoL). 2255 parents of children and adolescents with a mean age of 13.2, attending the 5th grade and 7th grade were inquired. The fit indexes indicate good fit to the data. Specifically, the final solution of the RMSEA was lower than .03, the upper limit of 90% confidence interval was lower than .05, and CFI was higher than .95. Results indicate that the current 52 items structure is invariant across gender and age group. The parents version of the Kidscreen-52 questionnaire constitutes a valid instrument to estimate parents perception of quality of life in their children.